Dinamika Penalaran Jaksa pada Pembuktian Bukti Elektronik: Studi Fenomenologi Forensik Digital (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
Digital transformation has significantly increased the use of electronic evidence as a primary source of proof in criminal proceedings. Although previous studies have extensively examined the legal admissibility and technical reliability of electronic evidence, limited attention has been given to how prosecutors construct legal reasoning when evaluating digital evidence in prosecutorial practice. This study aims to explore prosecutors' lived experiences in developing legal confidence toward electronic evidence and to propose the conceptual framework of Prosecutorial Digital Reasoning . The research adopts an interpretivist paradigm using a qualitative design based on Interpretative Phenomenological Analysis (IPA) . Data were collected through semi-structured interviews, document analysis, and non-participant observation involving prosecutors with substantial experience in handling criminal cases involving electronic evidence. Data analysis followed the IPA procedures of initial noting, emergent theme development, cross-case analysis, and conceptual synthesis using NVivo Release 14. The findings indicate that prosecutorial reasoning develops through an interpretative process integrating technological understanding, forensic validation, professional experience, collaboration with digital forensic experts, and strategic legal reconstruction. These findings provide the foundation for the proposed Prosecutorial Digital Reasoning framework, which conceptualizes the evaluation of electronic evidence as a dynamic and recursive cognitive-interpretative process. The study contributes to the literature on electronic evidence by extending existing normative and technical perspectives toward the cognitive dimension of prosecutorial decision-making. Practically, the proposed framework offers implications for strengthening prosecutorial competence, developing standardized electronic evidence evaluation guidelines, and enhancing institutional capacity to address the challenges of digital transformation within contemporary criminal justice systems.